Using Innovative Technologies and Techniques for Organizing Independent Student Work (Analysis of Foreign Experience) - Хорошайло, Олена Станіславівна (Educological discourse, 2014)
The article considers the problem of the organization of students’ independent work at higher educational institutions and the possibility of using foreign experience. The author analyzes some innovative technologies and techniques which can be used by teachers in educational process of higher education.